“The Dude Abides”: How The Big Lebowski Bowled Its Way from a Box Office Bomb to Nation-Wide Fests - Małecka, Katarzyna (Text Matters: A Journal of Literature, Theory and Culture, 2012)
Since Blood Simple, the first film they wrote and directed together, the Coen Brothers have been working their way up in the film world and, in spite of their outside-the-mainstream taste for the noir and the surreal, have earned a number of prestigious prizes. After Fargo, one of their most critically acclaimed films, expectations were high, and when the Brothers released their next bizarre venture, most critics rushed to measure it against Fargo’s success. Consequently, The Big Lebowski, the Coens’ 1998 neo-noir detective comedy, was considered an incoherent, “unsatisfactory” medley of genres and styles and a box office bomb, and nothing hinted that this unorthodox story of mistaken identity, featuring a pot-smoking, unemployed character named the Dude as its “hee-ro,” would gain a following. Yet, since its 1998 DVD release, The Big Lebowski has been hailed as the first cult film of the Internet, continuously inspiring versatile cultural phenomena as nonconformist in their nature as the movie itself. This essay examines particular factors which initially might have been responsible for alienating the audience only to help The Big Lebowski become a peculiar cultural event in later years. It looks at The Big Lebowski’s characters, the historical time and place of the film’s action as well as at various external historical events, phenomena, places and people such as, for example, the Port Huron Statement, the Reagan-Bush era, Los Angeles and its immigration issues, racial minorities, civil rights activists, the Western genre and, last but not least, Arnold Schwarzenegger. Reflecting the film’s oddities, this bag of cultural idiosyncrasies appears to provide some plausible explanations for The Big Lebowski’s unexpected, against-all-odds rise from the marginal position of a critical and commercial failure to the status of a cult classic and cultural landmark.